RANCANG BANGUN RANGKA DAN DESAIN PADA PALANG PINTU OTOMATIS MENGGUNAKAN RFID BERBASIS ARDUINO - Maulana, Rizky; Apnena, Riri Damayanti (Jurnal Mahasiswa Terapan, 2025)
In general, opening and closing large doorstops takes a lot of energy and time, and the security of residential doorstops that do not use a security system can make the occupants feel unsafe. One way to save energy and time for opening and closing large doorstops and security in housing is to use automatic doorstops using RFID as a sensor and security system. The way the RFID system works is to bring the RFID Tag closer to the RFID Reader. The RFID Tag will be read by the RFID Reader and the data read will be checked and processed by the Arduino UNO whether it matches the database or not. Arduino UNO will identify and adjust data from the RFID Tag. On the other hand, if the RFID is not verified, the bar will not open and the display "UNKNOWN DATA!" will appear. The Ultrasonic Sensor functions as a door latch safety to detect that the vehicle has actually entered which will send a signal to the driving motor so that the door latch closes completely.